A proposed forward clause slicing application - Khalil Awad; Mohammad Abdallah; Abdelfatah Tamimi; Amir Ngah; Hanadi Tamimi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The Clause slicing technique is static slicing techniques which also have forward and backward slicing methods. The Clause slice criteria are the clause and the clause number. In this paper, we have discussed the Clauser tool the forward clause slicing tool introduce some improvements to it. The Clauser mechanism divides the program code statement into clauses, depending on clause slicing rules, identifies the variables and built-in functions, then slices the clauses regarding the slice criterion that was entered by the user. Comparing to other static slicing techniques the clause slicing is more accurate and precise because it considers all the code in micro-level, where it focuses on every syntax in the code. The Clauser still needs to be enhanced to slice more code features.